Bibliometric Analysis: Adobe Flash Cs6 Research in Mathematics Learning - Ilham Muhammad; Christina Monika Samosir; Elmawati Elmawati; Febrinna Marchy (JPMI (Jurnal Pendidikan Matematika Indonesia), 2023)
The use of animation on Adobe Flash media in learning mathematics has many benefits, especially in helping students understand mathematics more meaningfully, connecting mathematics with the real world, visualizing, and understanding the importance of mathematics. This study aims to capture the landscape of previous research that is relevant to Adobe Flash in mathematics learning in the last decade, namely from 2012 to 2022 using bibliometric analysis with the help of the VOSviewer application. The Google Scholar database was used to search for data with the keywords "adobe flash" and "mathematics learning" which were then refined to become 72 publications. The trend of publications related to Adobe Flash in learning mathematics has increased from 2015 to 2018, while the most publications occurred in 2021 with 19 documents. Publications in 2018 have been cited in more than 150 citations. The focus of research related to Adobe Flash in learning mathematics is 1) problems, motivations and interests; 2) development, contextual teaching and elementary school; 3) outcomes and technology. The keyword "Adobe Flash" is not directly related to the keywords contextual teaching, android and stem. The new themes related to this field are pandemic, interest, e-learning, stem and primary school.